2018
DOI: 10.1063/1.5011645
|View full text |Cite
|
Sign up to set email alerts
|

Separating light absorption layer from channel in ZnO vertical nanorod arrays based photodetectors for high-performance image sensors

Abstract: Photoconductor arrays with both high responsivity and large ON/OFF ratios are of great importance for the application of image sensors. Herein, a ZnO vertical nanorod array based photoconductor with a light absorption layer separated from the device channel has been designed, in which the photo-generated carriers along the axial ZnO nanorods drive to the external electrodes through nanorod-nanorod junctions in the dense layer at the bottom. This design allows us to enhance the photocurrent with unchanged dark … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It can be found that at a bias voltage of 5 V, the light current reaches 62.0 μA, which is 10.2-times higher than the dark current (6.1 μA). At 1 V bias, the photocurrent is 3.4 μA, and the nanorod array prepared by Ma et al responds to 7.9 μA, but the UV light they used had a power intensity of 1 mW/cm 2 , 100-times higher than ours . The curves showing the response/recovery time (defined as 90% of the time required for photogenerated carrier generation and recombination) are carried out as shown in Figure (d).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It can be found that at a bias voltage of 5 V, the light current reaches 62.0 μA, which is 10.2-times higher than the dark current (6.1 μA). At 1 V bias, the photocurrent is 3.4 μA, and the nanorod array prepared by Ma et al responds to 7.9 μA, but the UV light they used had a power intensity of 1 mW/cm 2 , 100-times higher than ours . The curves showing the response/recovery time (defined as 90% of the time required for photogenerated carrier generation and recombination) are carried out as shown in Figure (d).…”
Section: Resultsmentioning
confidence: 98%
“…The method of spin-coating precursor solutions onto PET substrates coated with insertion finger electrodes was used by Hafiz et al, while this approach still requires heating to 150 °C to generate the seed layers . Ma et al prepared vertical nanorods for UV detection with a responsivity of 1.3 × 10 5 A/W; the processes are complex and high temperatures required to generate the ZnO seed layers are not suitable for flexible devices, and the authors also mentioned in their paper the difference in the mechanism of electron motion in different UV detectors. Chen et al fabricated horizontal ZnO nanorods, which unfortunately did not yield a desirable photocurrent:dark current ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly diverse applications are taking advantage of this platform – e. g . plasmonics, sensors, imaging, energy conversion and storage, electron‐field emission, and superhydrophobic surfaces – to capitalize on the extremely high surface‐to‐volume ratio and/or the sharp tips of the NNAs, in combination with the wide selection of materials ( e. g . metals, semiconductors, carbon, polymers, and composites) available to prepare the NNAs .…”
Section: Introductionmentioning
confidence: 99%
“…The wide direct bandgap of 3.37 eV and a large exciton binding energy of 60 meV of ZnO allow optically pumped ultraviolet (UV) lasing at room temperature . Thanks to their easy tailoring for the intrinsic optoelectronic attribute, , as well as the hybridization potentials with diverse functional materials, ZnO NWs have been configured as key components in the fields of spectral detection, , photoinverter, , solar cell, electrically pumped lasing, and piezo-phototronics . Till now, many more studies have focused on the ensemble of NWs (e.g., array type) as compared to those on a single NW, which is simply due to the intrinsic difficulties for fabricating and characterizing individual NWs.…”
mentioning
confidence: 99%
“…Till now, many more studies have focused on the ensemble of NWs (e.g., array type) as compared to those on a single NW, which is simply due to the intrinsic difficulties for fabricating and characterizing individual NWs. However, a single NW usually gives rise to better performances than ensemble, in particular, on photodetection, , which has not yet been fully understood. Therefore, an in-depth understanding of intrinsic properties of single NW is crucial for device applications.…”
mentioning
confidence: 99%